Hubungan antara Self-Compassion dan Compassion for Others pada Guru SD ‘X’ di Kota Bandung - Marlyna Candra Wiguna; Ellen Theresia (Universitas Kristen Maranatha, 2020)
This study aims to determine the relationship between self-compassion and compassion for others in elementary school teacher. Fifty teachers participated and filled the self-compassion and the compassion for others questionnaires. Using the Pearson correlation test, the correlation results obtained 0.230 (sig = 0.054, ?0.05), which means that there is no relationship between self-compassion and compassion for others. This study also found that the majority of teachers in ‘X’ elementary school have low self-compassion and compassion for others. For further research is useful to examine the relationship among components of self-compassion and compassion for others. The principal of ‘X’ elementary school has to consider a counseling program to help the teachers reduce and regulate perceived stress and overcome the difficulties so that it is more possible for the teachers to improve self -compassion and compassion for others. Keywords: Self-Compassion, Compassion For Others, teacher, elementary school